Flexible learning templates for dispersed learners: Expanding the role of the content expert without pain - Michael Alford; Carolynn Oleniuk; Sharon Roffey (Flexible Learning Association of New Zealand, 2012)
The Office of the United Nations High Commissioner for Refugees (UNHCR) provides training for staff at 200 locations worldwide and in an extreme range of conditions. This article describes the processes involved in undertaking the development of a series of easy-to-use templates for the development of learning and training materials by UNHCR staff. The templates provide a repertoire of tools and resources for subject matter experts wishing to develop self-directed or flexible learning guides for particular groups of learners. Challenges facing the creators during design and implementation phases are discussed and a set of lessons learned from both phases is outlined.